Redes sociais: prevenção e recaída no tratamento de dependentes químicos - Gutjahr, Méris (2010)
Most cases of people using some kind of psychoactive substance elapses from the expectation of obtaining some benefit from it, by the pleasure experience or pain relief. Many of those people become dependent along life and many of them will need some kind of treatment to get to stop using psychoactive substances. The use of psychoactive substances causes great changes in the social and family relationships and even physical and neurological changes in the own user. Several treatment modalities exist, and they may be effective or not. Who basically determines the effectiveness of the treatment is the dependent, for his own wish of wanting to stop using psychoactive substances. However, it is possible that external elements are risk factors for the relapse or serve as protection. The social reinsertion, when well worked, already during the internment, it can be protection factor for maintenance of the abstinence. The recovery that only focuses the abstinence, without worrying with the social environment, the life and attitudes changes tends to not to have so much success. The social nets acted in the potential of the family, of the groups of mutual help and of the religious community, when well articulate, prepared and connected they are preventive of the relapse.